PELATIHAN PENANGANAN VIRUS KOMPUTER PADA KOMUNITAS PEKON BUMI REJO KECAMATAN PAGELARAN KABUPATEN PRINGSEWU - Eka Ubaya Taruna Ruaf; Suhartina Suhartina; Riko Herdiansah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Everyday life of society has changed significantly as a result of technological advances. Not to mention the development of viruses that can infect a computer or laptop, the need to deal with viruses that can harm the computer and must be handled appropriately, but there are still several ways to eliminate them before causing serious damage. The operating system and applications can be damaged by viruses. Therefore, it is very important for the Pekon Bumi Rejo community in Pagelaran District, Pringsewu Regency to have the necessary expertise to fight this virus. The suggested solution is to teach the public how to deal with viruses on a computer through this training so that they can use knowledge and understanding to protect their own computer or laptop from the invading virus. The implementation of this community service activity uses digital modules, through training that is used to put community service projects into action. Keywords: Training, Handling, Viruses, Computers, Society